Everyday Lives in China's Cold War Military-Industrial Complex - Xu, Youwei. author. aut Link
XXVII, 371 p. 29 illus., 12 illus. in color.
Keywords: This book translates and contextualizes the recollections of men and women who built, lived, and worked in some of the factory compounds relocated from China’s most cosmopolitan city—Shanghai. Small Third Line factories became oases of relatively prosperous urban life among more impoverished agricultural communities. These accounts, plus the guiding questions, contextual notes, and further readings accompanying them, show how everyday lives fit into the sweeping geopolitical changes in China and the world during the Cold War era. Furthermore, they reveal how the Chinese Communist Party’s military-industrial strategies have shaped China’s economy and society in the post-Mao era. The approachable translations and insight into areas of life rarely covered by political or diplomatic histories like sexuality and popular culture make this book highly accessible for classroom use and the general-interest reader. Xu Youwei is Professor of History at Shanghai University, China. Y. Yvon Wang is Associate Professor of History at the University of Toronto, Canada. .